Residential satisfaction and living experience in low-cost housing within tropical climates: a case study of Kuching, Sarawak, Malaysia - King Kuok, Kuok; Po Chan, Chiu; Mohd Elfy, Mersal; Rezaur, Rahman; Khairul Anwar, Mohamad Said (Springer Nature, 2025)
Amidst escalating housing prices and inflation in Sarawak, the government has implemented four schemes to assist low-income families in securing affordable homes. However, challenges persist in delivering quality housing for this demographic. A questionnaire survey was conducted to assess residential satisfaction, focussing on the principal factors and impact of socio-demographic characteristics on residential contentment. A comprehensive questionnaire survey was administered to 100 residents across three low-cost housing communities in Kuching, Sarawak. The findings reveal that 31.7% of respondents earn below RM2000 per month, while 29.6% have incomes between RM2000 and RM2999, positioning them in the lower income brackets. A substantial 78.3% of respondents reside in low-cost flats. Three-room units, constituting 43.7% of low-cost housing, are the most feasible option for affordability and